Coolie from Marxist Perspective in Mulk Raj Anand’s Coolie - Adhikari, Bina (Pursuits: A Journal of English Studies, 2023)
The aim of this article is to analyze critically about Mulk Raj Anand's novel Coolie from Marxist perspective. Although Marxist theory of literature developed out of Marx’s and Engel's general remarks concerning culture, art and literature in relation to their discussion about social economic and political questions as a literary theory. So Marxist criticism can be taken as the twentieth century phenomenon. Coolie is a great work of art and a number of themes and ideas have been woven into its texture. However, its central theme is the exploitation of the poor and the under-privileged by the forces of capitalism, industrialism and colonialism. This theme had been studied in depth with reference to Munoo, a poor, helpless orphan, who is denied his fundamental right to life and happiness, who is exploited and made to suffer, till he dies of consumption. Munoo is not the only victim of such exploitation, the novelist makes it quite clear, that such exploitation and denial of life and happiness is the lot of the poor everywhere in India, whether in villages or big cities like Daulatpur and Bombay. The lot of the poor is equally wretched and miserable whether in rural or urban India.